Detection of quantitative trait loci for heading date and temperature responsiveness in a re‐sequenced, recombinant inbred line of japonica rice from Heilongjiang province, china. (22nd October 2021) - Jiang, Shukun; Wang, Lizhi; Yang, Xianli; Zhang, Xijuan; Meng, Ying; Li, Mingxian; Chi, Liyong; Li, Zhongjie; Zhao, Qian; Liu, Youhong; Ma, Yuling; Ding, Guohua; et al.
Abstract: The hereditary basis and identification of novel genes of heading date have significant implications for japonica rice improvement in northeast China, especially in Heilongjiang province. A re‐sequenced recombinant inbred line (RIL) population derived from the cross between Lijiangxintuanheigu (LTH) and Shennong 265 (SN265) was used to detect the genetic basis for the RIL in 2017 and 2018. Fourteen heading date quantitative trait loci (QTLs), including nine in 2017 and thirteen in 2018, were detected with a linkage map containing 2, 818 bin markers. They were distributed on chromosomes 3, 4, 6 and 9–11 with 9.34%–25.26% phenotypic variations. The QTLs qHD3a, qHD4a, qHD4b, qHD4c, qHD9b, qHD10, qHD11c and qHD11d were identified in both years. The qTRS1, qTRS3a ( qHD3a ), qTRS3b (qHD3b) and qTRS9 (qHD9a) alleles from LTH and the qTRS4 allele from SN265 were identified by controlling the temperature responsiveness in the RIL population. The explained phenotypic variation in these five QTLs varied from 14.52% to 26.31%. In order to accurately determine the difference in heading date under different temperature conditions, the RILs and two parents were grown in a phytotron. Four QTLs controlling temperature responsiveness were identified on chromosomes 3, 6 and 9, including qTRS3a ( qHD3a ), qTRS3b ( qHD3b ), qTRS6 and qTRS9 ( qHD9a ). In a different environment, qTRS3a ( qHD3a ), qTRS3b ( qHD3b ) and qTRS9 ( qHD9a ) were detected. A comparison of chromosomal locations between the QTLs detected in this study and heading date genes previously cloned indicated that DTH3, Hd16, RFL, HAF1, Ehd2 and RBS1 might be candidate genes for them. The four major heading date genes ( Hd1, Ghd7, Ghd7.1 and Ghd8 ) affecting ecogeographical adaptation were sequenced between SN265 and LTH. SN265 carried a functional Hd1 haplotype, a weak functional Ghd7 haplotype, a weak functional Ghd7.1 haplotype and a weak functional Ghd8 haplotype. LTH also carried functional Hd1 haplotype, a weak functional Ghd7 haplotype, a non‐functional Ghd7.1 haplotype and a non‐functional Ghd8 haplotype. The combinations of the Hd1, Ghd7, Ghd7.1 and Ghd8 alleles in SN265 and LTH largely defined their short heading date under long‐day conditions. The selection of heading date gene combinations with functional Hd1 alleles and non‐functional alleles or weak functional alleles of Ghd7, Ghd7.1 and Ghd8 would be an effective way to improve japonica rice with proper heading days in Northeast China. The novel QTLs detected in this study could also become a valuable source for designing the appropriate heading date in Northeast China japonica rice.